Partizipation migrantisch markierter Bürgerinnen in der Süddeutschen Zeitung – eine diskursanalytische Sondierung - Madlen Pilz (Geographica Helvetica, 2020)
Based on the discourse analysis of articles collected between 2010 and 2016 from the Süddeutsche Zeitung – a leading local and German national newspaper – my aim is to reconstruct the central conditions limiting or enabling the participation of those citizens in the public discourse who are generally constructed as ,,migrants“. Therefore, I analyse the central elements of the discourse around the subject migration/integration. My analysis is guided by the ,postmigrant debate`, in particular by the approaches of the ,differential inclusion` of migrantised groups and their ,struggles of migration` combining it with critical race debates. My aim is to outline the different discursive ways that allow migrantised citizens to participate in public meaning making, and the ways, they use to contest majoritarian views. My analysis reveals their critical reconsideration of the system of differentiated inclusion, which is organizing the majoritarian discourse and ,migrants` everyday lives. While the journalistic strategy exemplified within the analysis is working in support of the ,migrant's perspectives`, it simultaneously acts to normalize majoritarian position contra migration.
Keywords: 320